Credible as Evidence? Multilayered Audience Reception of Narrative Arguments - Bubikova-Moan, Jarmila (Informal Logic)

(untitled) (Informal Logic, 2021)
Building on a view of both narration and argumentation as dynamic concepts, this paper considers ways of assessing the credibility of narrative arguments constructed in empirical examples of conversational discourse. I argue that the key in any such exercise is to pay close attention to both structural and pragmatic details, particularly how conversational storytelling gets embedded in the surrounding discourse and how the way this is discursively accomplished vis-à-vis the narrators’ multilayered audience may be reflective of their argumentative goals.